2005
DOI: 10.2134/jeq2005.0029
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Reuse and Sustainability: The Fate of Organic Compounds in Land‐Applied Waste

Abstract: Land application systems, also referred to as beneficial reuse systems, are engineered systems that have defined and permitted application areas based on site and waste characteristics to determine the land area size requirement. These terrestrial systems have orders of magnitude greater microbial capability and residence time to achieve decomposition and assimilation compared with aquatic systems. In this paper we focus on current information and information needs related to terrestrial fate pathways in land … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…The higher frequency of detection as well as higher concentrations of estrogens seen in lettuce compared to spring onion and green bell pepper suggested that either the lettuce roots were better capable of directly taking up the estrogens and translocating them into leaves or estrogens were being directly deposited on foliage during irrigation or as dust. Other studies have found that nonagricultural organic compounds associated with waste are more likely to be found as deposits on plant foliage left by waste application rather than through translocation from shoots (Overcash et al 2005). No accumulation of estrogens in plant tissue was observed during the sampling period.…”
Section: Estrogen Concentrationsmentioning
confidence: 76%
“…The higher frequency of detection as well as higher concentrations of estrogens seen in lettuce compared to spring onion and green bell pepper suggested that either the lettuce roots were better capable of directly taking up the estrogens and translocating them into leaves or estrogens were being directly deposited on foliage during irrigation or as dust. Other studies have found that nonagricultural organic compounds associated with waste are more likely to be found as deposits on plant foliage left by waste application rather than through translocation from shoots (Overcash et al 2005). No accumulation of estrogens in plant tissue was observed during the sampling period.…”
Section: Estrogen Concentrationsmentioning
confidence: 76%
“…Antibiotics, an important class of contaminants falling into this category, have been detected widely in the environment including in MSS ( n = 14), even when their sorption coefficients are low (Batt et al, 2006; Kummerer, 2003; McClellan and Halden, 2010). Leaching of antibiotics from soils has been identified as one of the most important pathways for contamination of water bodies (Overcash et al, 2005; ter Laak and Gebbink, 2006; Thiele-Bruhn, 2003). Batch sorption experiments conducted in the laboratory showed that the interaction between antibiotics and soil particles were governed predominantly by solution pH (Hari et al, 2005; ter Laak and Gebbink, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…General summaries of each topic's “state‐of‐the‐science” and research priorities are given below. Details are provided in the individual plenary papers on Nutrients (Pierzynski and Gehl, 2005), Metals (Basta et al, 2005), Organics (Overcash et al, 2005), Pathogens (Gerba and Smith, 2005), and Interpreting Science in the Real World (Bastian, 2005).…”
Section: Topic Summariesmentioning
confidence: 99%